THE CHALLENGE OF PORTUGUESE LANGUAGE TEACHING IN TIMES OF LIQUID TEXTUALITY - Rodrigo Catarin, Cristiano; Cristine de Jesus Lima, Evelin; Cristina Rangel Gusmão, Kelly; Claudio de Medeiros Silva, Luís; Martins Abachioni, Mauricio (Revista Gênero e Interdisciplinaridade, 2022)
Currently, one of the biggest challenges of teaching Portuguese in basic education is the dynamics contained in linguistic processes through digital information and communication technologies (TDIC). The National Curricular Common Base - BNCC, promotes a mitigating discourse in this scenario, pointing out that its demands are in complete harmony with modern guidelines for reading, writing and textual production, considering, including the development of new textual genres from virtual supports in literacy records, symbols and other interpretive signs of language. In this sense, the present work, characterized by a bibliographical rereading, aims to visit and analyze the main discussions about the existence or not of new textual genres in the face of the speed and diversity present in social communication. In addition, from these indicators, it was possible to register the confrontation of specific works regarding new textual genres with the normative proposal established by the BNCC in the current teaching process in the country.